The internal nest architecture and thermoregulation of geniotrigona thoracica (Hymenoptera: Meliponini) - Farisya , M.S.; Kelly N. ,; Kumara T.K., (Pusat Sistematik Serangga ,UKM, 2013)

(untitled)
The internal nest structure of stingless bee comprise of broods, honey pots and pollen pots whereas thermoregulation has significant ecological consequences to the stingless bee because the internal heat generation enables bees to forage under colder surrounding temperature. In this study, colonies (n=6) of Geniotrigona thoracica were measured for its brood cell size, volume of honey, foraging frequency, internal and external temperature, size of honey pot and pollen pot monthly from July 2013 - September 2013. Results showed the diameter and height of brood cells, honey pots and pollen pots were 3.9 ± 0.72 mm, 6.1 ± 1.29 mm, 15.1 ± 4.02 mm, 24.4 5.31 mm, 22.9 ± 5.37 mm and 16.25 ± 6.58 mm, respectively. The mean honey production was 206.8 ± 25.27 ml. The mean internal and external temperatures were 26.7 ± 0.15 °C and 26.6 ± 0.36 °C respectively. The foraging frequencies for this species were at peak from 10 a.m — 12 p.m.